Cellular and molecular maturation in fetal and adult ovine calcaneal tendons. Issue 2 (25th December 2014) - Russo, Valentina; Mauro, Annunziata; Martelli, Alessandra; Di Giacinto, Oriana; Di Marcantonio, Lisa; Nardinocchi, Delia; Berardinelli, Paolo; Barboni, Barbara
Abstract Processes of development during fetal life profoundly transform tendons from a plastic tissue into a highly differentiated structure, characterised by a very low ability to regenerate after injury in adulthood. Sheep tendon is frequently used as a translational model to investigate cell‐based regenerative approaches. However, in contrast to other species, analytical and comparative baseline studies on the normal developmental maturation of sheep tendons from fetal through to adult life are not currently available. Thus, a detailed morphological and biochemical study was designed to characterise tissue maturation during mid‐ (2 months of pregnancy: 14 cm of length) and late fetal (4 months: 40 cm of length) life, through to adulthood. The results confirm that ovine tendon morphology undergoes profound transformations during this period. Endotenon was more developed in fetal tendons than in adult tissues, and its cell phenotype changed through tendon maturation. Indeed, groups of large rounded cells laying on smaller and more compacted ones expressing osteocalcin, vascular endothelial growth factor (VEGF) and nerve growth factor (NGF) were identified exclusively in fetal mid‐stage tissues, and not in late fetal or adult tendons. VEGF, NGF as well as blood vessels and nerve fibers showed decreased expression during tendon development. Moreover, the endotenon of mid‐ and late fetuses contained identifiable cells that expressed several pluripotent stem cell markers [Telomerase Reverse Transcriptase (TERT), SRY Determining Region Y Box‐2 (SOX2), Nanog Homeobox (NANOG) and Octamer Binding Transcription Factor‐4A (OCT‐4A)]. These cells were not identifiable in adult specimens. Ovine tendon development was also accompanied by morphological modifications to cell nuclei, and a progressive decrease in cellularity, proliferation index and expression of connexins 43 and 32. Tendon maturation was similarly characterised by modulation of several other gene expression profiles, including Collagen type I, Collagen type III, Scleraxis B, Tenomodulin, Trombospondin 4 and Osteocalcin. These gene profiles underwent a dramatic reduction in adult tissues. Transforming growth factor‐<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3gsn8g9r" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />β </alternatives>1 expression (involved in collagen synthesis) underwent a similar decrease. In conclusion, these morphological studies carried out on sheep tendons at different stages of development and aging offer normal structural and molecular baseline data to allow accurate evaluation of data from subsequent interventional studies investigating tendon healing and regeneration in ovine experimental models.